A Visual Semiotic Analysis of Multicultural Values in An Indonesian English Textbook for Primary School Students: A Qualitative Study - Melya Putri Astari; Bambang Widi Pratolo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Most previous studies have analyzed multicultural values from various countries and school levels, yet not extensively examined the Indonesian textbooks for young learners. To fill this gap, this study conducts a visual semiotic analysis to explore the representation of multicultural values in an Indonesian English textbook for primary school students. Utilizing Barthes' visual semiotic theory, the research examines images from the textbook "My Next Words" focusing on four multicultural value keys: respecting other people’s traditions (ROPT), appreciating other people’s perspectives (AOPP), appreciating other people’s cultural products (AOPCP), and appreciating women’s equal rights (AWER). The first finding shows that appreciating women's equal rights (AWER) is the most frequently represented multicultural value in the textbook while appreciating other people’s cultural products is the least represented. The second finding indicates that the images in the textbook primarily represent universality across cultures (UC), with no portrayal of intercultural interaction (ICI). The study concludes that the textbook has an imbalanced representation of multicultural values. Therefore, textbook authors and teachers must address this imbalance. Textbooks should offer more images that represent balanced multicultural values. Meanwhile, teachers should actively engage in selecting appropriate textbooks, reviewing and evaluating multicultural values and cultural references, and providing feedback to publishers. By comparing similarities and differences from different cultures and countries, learning activities can improve students' multicultural awareness and enhance their intercultural communicative competence (ICC).